Perancangan Hotel di Medan dengan Pendekatan Arsitektur Tropis - Roberto Ghadvent Tampubolon; Morida Siagian (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
The Medan city is one of the largest cities in Indonesia with many economic and tourist activities. The Medan city is one of the gateways for Indonesian businessmen and tourists, especially in North Sumatra. This requires an accommodation that can be a lodging solution for business people and tourists who are doing temporary interests in the city of Medan. This has the potential to design a hotel as a temporary lodging solution for business people and tourists in the city of Medan. The hotel design uses problem solving methods that are focused on solving existing problems, starting from the formulation stage, data collection, analysis to synthesis using survey techniques, literature studies and comparative studies. So that through the design of this hotel, it can be the right lodging solution in the city of Medan with a Tropical Architecture approach that is able to provide comfort for users. Hotel design pays attention to the availability of infrastructure and utilities to support human needs in a design that is able to adapt to the surrounding environment.